Long Distance Endovascular Growth of Jugulotympanic Paraganglioma Evident in 68Ga-DOTATATE PET but Concealed on CT. (February 2017) - Avramovic, Nemanja; Weckesser, Matthias; Velasco, Aglaé; Stenner, Markus; Noto, Benjamin
Abstract : Abstract: A 60-year-old woman was referred to contrast-enhanced CT for evaluation of jugular vein thrombosis incidentally detected by ultrasound. Contrast-enhanced CT showed an enhanced tumor of the right skull base highly suspicious of jugulotympanic paraganglioma. However, the jugular veins showed a nearly symmetric contrast enhancement without clear evidence of thrombosis. Consecutive 68 Ga-DOTATATE PET/CT depicted high tumor uptake, which comprised the entire internal jugular vein. Endovascular growth of paraganglioma might be missed on contrast-enhanced CT because of high vascularization of the lesion. 68 Ga-DOTATATE PET is suited for accurate determination of tumor extent.